Impacts of CO2-induced seawater acidification on coastal Mediterranean bivalves and interactions with other climatic stressors - Range, Pedro (2014)
The effects of seawater acidification caused by increasing concentrations of atmospheric carbon dioxide (CO2), combined with other climatic stressors, were studied on 3 coastal Mediterranean bivalve species: the mussel Mytilus galloprovincialis and the clams Chamelea gallina and Ruditapes decussatus. CO2 perturbation experiments produced contrasting responses on growth and calcification of juvenile shells, according to species and location. In the Northern Adriatic (Italy), long-term exposure to reduced pH severely damaged the shells of M. galloprovincialis and C. gallina and reduced growth for the latter species. Seawater in the Ria Formosa lagoon (Portugal) was consistently saturated in carbonates, which buffered the impacts on calcification and growth. After 80 days, no shell damage was observed in Portugal, but mussels in the acidified treatments were less calcified. Reduced clearance, ingestion and respiration rates and increased ammonia excretion were observed for R. decussatus under reduced pH. Clearance rates of juvenile mussels were significantly reduced by acidification in Italy, but not in Portugal. Both locations showed a consistent trend for increased ammonia excretion with decreasing pH, uggesting increased protein catabolism. Respiratory rates were generally not affected. Short-term factorial experiments done in Italy revealed that acidification caused alterations in immunological parameters of adult bivalves, particularly at temperature and salinity values far from the optimal for the species in the Mediterranean. Overall, our results showed large variations in the sensitivities of bivalves to climatic changes, among different species and between local populations of the same species. Expectations of impacts, mitigation and adaptation strategies have to consider such local variability.